(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The Hindu majority in India is particularly susceptible to and has traditionally been mobilized along caste lines since caste is the most pervasive social institution in Indian society. Despite the constitutional system’s clear condemnation of caste, caste mobilization in all its manifestations has dominated party politics. Even in India’s political system, this has been going on for quite some time. The Bhakti Party of India (BJP) promotes a Hindu nationalist philosophy known as Hindutva. Hinduism is an ideology that advocates for the preservation and participation of Hindu culture in state life. Hindu fundamentalism is the inevitable outcome of Hindutva, a political philosophy in and of itself. The core tenet of Hindutva ideology is the idea that Hindus in India should be seen as a single country and regional entity. A Hindu state caliphate, as advocated for by the BJP party’s head, would elevate Hindus to the position of dominant force in India. Another tenet of this philosophy is the idea that Hindutva has always been a part of Hindustani culture. This political philosophy seeks to convert India into a Hindu nation and legitimizes all forms of discrimination against marginalized communities. The abolition of this philosophy would amount to the destruction of Hindu civilization. A growing number of people are joining the Bharatiya Janata Party (BJP), which currently has 180 million members—far more than the Congress Party’s 20 million.